2016
DOI: 10.14260/jemds/2016/1072
|View full text |Cite
|
Sign up to set email alerts
|

Study on Evaluation and Management of Hand Injuries

Abstract: BACKGROUNDHand injuries are common accounting for nearly 10% of hospital emergency department visits. Aim of this study is to evaluate the peculiarities of the epidemiology of the various causes of hand injury in our locality, various pattern of presentation, various treatment modalities adopted in our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
2
1
0
1
Order By: Relevance
“…Consistent with previous studies ( 18 , 19 ), the findings of this study established that the majority of patients with tendon injuries were young (mean age 34.98 years), male (79.24%), and blue-collar workers (52.47%). In addition, 35.5% of the sample had fine jobs that relied on flexible hand functions, such as computer operators and handicraft makers.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies ( 18 , 19 ), the findings of this study established that the majority of patients with tendon injuries were young (mean age 34.98 years), male (79.24%), and blue-collar workers (52.47%). In addition, 35.5% of the sample had fine jobs that relied on flexible hand functions, such as computer operators and handicraft makers.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the dominant hand (50.5%) was affected somewhat more often than the non-dominant hand, which was similar to the findings reported by Thangavelu et al, [14] although other studies reported similar or less frequent rates. [13,17,18] The dominant hand is usually injured when using a sharp object directly or catching a falling object.…”
Section: Discussionsupporting
confidence: 91%
“…[6] Consistent with the previous studies, the findings obtained in this study demonstrated that most of the patients with flexor tendon injuries were young (mean age, 31.8), male (79.4%), and blue-collar workers (50.0%). [13,14] Proper injury management to optimize the long-term functional outcomes and economic burden are important among patients with these characteristics, who potentially have a prolonged working life expectancy requiring adequate hand function. [15] The rate of work-related injuries based on formal records in our study was 17.5%, which was markedly lower than that reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Прочность сухожильного шва зависит от следующих параметров: вид шовного материала; его калибр; количество нитей, проходящее через поперечник сухожилия; конфигурация петли; расстояние отступа от конца сухожилия; дополнительное натяжение места сухожильного контакта и расположение узла [10,11,12]. Исследования последних 20 лет были сфокусированы на вопросах изучения видов сухожильных швов и патоморфологии репарации сухожилий, но биомеханические свойства шовного материала при первичном восстановлении сухожилий сгибателей изучены недостаточно.…”
Section: гений ортопедии 2024;30(1)unclassified